Telangana State Micro-irrigation Project to address the water scarcity in the state - Rao, V Praveen; Ramulu, V (Indian Farming, 2020)
Irrigation of crops using inefficient gravity irrigation is a major impediment to optimizing productivity to majority of small and marginal farmers world over including, Telangana. Therefore, Government of Telangana’s investment in TSMIP - to strengthen the farmers hands with efficient drip irrigation and fertigation tools through 80-100% subsidies is aimed at promoting highly productive yet climate-smart agriculture. Providing means to small and marginal farmers to use innovative and efficient drip irrigation and fertigation technologies in crop production is a key to averting water scarcity, increasing agri- horticultural productivity, incomes and household food security. Efficient drip irrigation also broadens farmers’ crop choices and enables them to grow highervalue vegetables and fruits for higher farm profitability. lt also generates employment for people both with and without land, since more people are needed to harvest, process, and market the crops and to supply farm inputs. The project paves the way for other similar placed states to follow and adopt similar projects.